2005
DOI: 10.1002/bit.20622
|View full text |Cite
|
Sign up to set email alerts
|

The use of multi‐parameter flow cytometry to study the impact of limiting substrate, agitation intensity, and dilution rate on cell aggregation during Bacillus licheniformis CCMI 1034 aerobic continuous culture fermentations

Abstract: The main objective of this work was to establish those factors either physical (power input) or chemical (limiting substrate or dilution rate) that enhance cell aggregation (biofilm or floc formation) and cell physiological state during aerobic continuous cultures of Bacillus licheniformis. Glucose-limited steady-state continuous cultures growing at a dilution rate between 0.64 and 0.87/h and 1,000 rpm (mean specific energy dissipation rate (epsilonT) = 6.5 W/kg), led to the formation of a thin biofilm on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Likewise, a dual PI-EB staining showed that carbonlimitation induced changes in the physiological state of E. coli expressing a heterologous membrane protein during fed-batch cultures [145]. By monitoring individual Bacillus licheniformis cells, the inherent complex heterogeneity of microbial cultures even during the 'steady-state' of continuous culture fermentations was demonstrated [131,302]. In those works, the effect of starvation and lactose and glucose pulses on cell physiology during the steady state was studied by using PI and DiOC 6 (3) simultaneously, showing clear differences.…”
Section: Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a dual PI-EB staining showed that carbonlimitation induced changes in the physiological state of E. coli expressing a heterologous membrane protein during fed-batch cultures [145]. By monitoring individual Bacillus licheniformis cells, the inherent complex heterogeneity of microbial cultures even during the 'steady-state' of continuous culture fermentations was demonstrated [131,302]. In those works, the effect of starvation and lactose and glucose pulses on cell physiology during the steady state was studied by using PI and DiOC 6 (3) simultaneously, showing clear differences.…”
Section: Bacteriamentioning
confidence: 99%
“…For example, dead or dormant cells in high proportion may have a detrimental effect on the synthesis of the desired products or process efficiency [4,21,302]. That is, to fully understand and to optimize bioprocesses, it is necessary to consider the distribution of structural and functional cell properties within microbial populations [318].…”
Section: Theoretical Applications: Kinetic Modellingmentioning
confidence: 99%
“…MPF assays have been developed to distinguish physiological states of cells between modes of fermentation (batch, fed-batch versus continuous) [35 ], under conditions of substrate starvation [36], under varying bioprocessing conditions (dilution rate, agitation rate) [37 ], and upon induction to express recombinant proteins [38]. For example, a light scattering (LS), PI, and Bis-oxonol (BOX) assay was used to assess single-cell physiology and culture heterogeneity during fed-batch, batch, and continuous culture cultivations [35 ].…”
Section: Mpf To Analyze Sort and Develop Microbial Complex Phenotypementioning
confidence: 99%
“…MPF and cell sorting made possible to detect and quantify population heterogeneity induced by acidadapting cultures (i.e. viable, injured, and nonviable), and then to assess the population and single-cell responses and kinetics of death upon subsequent Flow cytometry for bacteria Tracy, Gaida and Papoutsakis 93 Comparing modes of fermentation DiOC 6 (3) and PI Membrane potential and permeability [36] Automated process control FSC, PI, FITC and GFP Size, membrane permeability, total protein and product [41] Processing parameter effects DiOC 6 (3) and PI Membrane potential and permeability [37 ] Analysis of metabolite and general stress physiology Substrate, product and byproduct stress…”
Section: Analysis Of Metabolite and Other Stress Responses And Theirmentioning
confidence: 99%
“…However, flow cytometers have now been coupled to a variety of input systems. For example, automation of delivery systems of flow cytometers is leading to their use with bioreactors that can be monitored continually (42,43), with multwell plates (see below), with subsecond reaction kinetics (10), and with devices that produce shear forces on cells or cell aggregates to model the environment of flowing blood (44,45).…”
Section: Sample Handling and Automationmentioning
confidence: 99%